2015
DOI: 10.1090/tran/5566
|View full text |Cite
|
Sign up to set email alerts
|

Finite cyclic group actions with the tracial Rokhlin property

Abstract: Abstract. We give examples of actions of Z/2Z on AF algebras and AT algebras which demonstrate the differences between the (strict) Rokhlin property and the tracial Rokhlin property, and between (strict) approximate representability and tracial approximate representability. Specific results include the following. We determine exactly when a product type action of Z/2Z on a UHF algebra has the tracial Rokhlin property; in particular, unlike for the strict Rokhlin property, every UHF algebra admits such an actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 30 publications
0
36
0
Order By: Relevance
“…The proof of Proposition 3.5 in [55] shows that there exists x ∈ K 1 (A ⋊ α Z 2 ) with x = 0 such that K 1 ( α)(x) = −x. It is shown in Proposition 5.4.1 in [5] that A ⋊ α Z 2 is isomorphic to the tensor product of the Bunce-Deddens algebra of type 2 ∞ with A, so in particular K 1 (A ⋊ α Z 2 ) does not have any 2-torsion.…”
Section: Definition 22 Letmentioning
confidence: 99%
See 1 more Smart Citation
“…The proof of Proposition 3.5 in [55] shows that there exists x ∈ K 1 (A ⋊ α Z 2 ) with x = 0 such that K 1 ( α)(x) = −x. It is shown in Proposition 5.4.1 in [5] that A ⋊ α Z 2 is isomorphic to the tensor product of the Bunce-Deddens algebra of type 2 ∞ with A, so in particular K 1 (A ⋊ α Z 2 ) does not have any 2-torsion.…”
Section: Definition 22 Letmentioning
confidence: 99%
“…is torsion free by the claim above, part (7) in Proposition 3.16 implies that K 0 (A ⋊ α Z 2 ) is also torsion free. However, this contradicts part (6) of Proposition 4.2 in [55], where it is shown that K 0 (A ⋊ α Z 2 ) has torsion isomorphic to Z 2 . This contradiction implies that dim c Rok (α) = 2, as desired.…”
mentioning
confidence: 93%
“…5. (See also[35, Example 2.9].) Therefore α is not cocycle conjugate to ν Z2 because W 2 ⋊ α Z 2 is not isomorphic to W 2 .…”
mentioning
confidence: 99%
“…In [27] it was shown that for G = Z/2Z the positive cone in K 0 (B θ ) coincides with the preimage of the positive cone in K 0 (A θ ) under the natural homomorphism K 0 (B θ ) → K 0 (A θ ) (in other words, it consists of all elements x ∈ K 0 (B θ ) such that tr * (x) > 0, where tr * : K 0 (B θ ) → R is the homomorphism induced by the trace). As was pointed to us by Chris Phillips, similar statement is also known to hold for other groups G. Namely, it follows from the fact that the corresponding crossed products are simple AH algebras with slow dimension growth and real rank zero (see Theorems 8.11 and 9.10 of [20]). …”
Section: 4mentioning
confidence: 58%